1985
DOI: 10.1530/acta.0.1090393
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of ascorbic acid in the adrenal of the rat

Abstract: Fifteen days after hypophysectomy of rats the concentrations of ascorbic acid (AA) in adrenals, liver, blood and urine are lower than in normal rats or in rats 1 day after hypophysectomy. Despite the low levels the percentage AA depletion after administration of ACTH and the subsequent repletion to the pre-ACTH level are normal. Lack of corticosteroids is not the cause of the low AA levels, as shown by experiments in 15 days adrenalectomized rats and in rats treated with low doses of dexamethasone.Fifteen days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Therefore, it is assumed that the damaged liver of VE-D-fed rats with WIRS releases ascorbic acid accumulated in the liver into the bloodstream more easily than the damaged liver of N-fed rats with WIRS. In addition, it has been shown in rats with a single administration of ACTH that ascorbic acid is released from the adrenal gland into the bloodstream (22). It has also been shown that human adrenal glands secrete ascorbic acid in response to ACTH (23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is assumed that the damaged liver of VE-D-fed rats with WIRS releases ascorbic acid accumulated in the liver into the bloodstream more easily than the damaged liver of N-fed rats with WIRS. In addition, it has been shown in rats with a single administration of ACTH that ascorbic acid is released from the adrenal gland into the bloodstream (22). It has also been shown that human adrenal glands secrete ascorbic acid in response to ACTH (23).…”
Section: Discussionmentioning
confidence: 99%
“…Serum ascorbic acid concentration in rats exposed to WIRS for a 6‐h period began to increase 0.5 h after the onset of the stress and continued to increase thereafter, reaching 2.5‐fold higher than that concentration in unstressed rats at 6 h. In addition, the content of adrenal ascorbic acid was well correlated with the concentration of serum ascorbic acid in a negative fashion in all stressed rats. It is known that a single treatment of rats with ACTH causes a rapid ascorbic acid depletion in the adrenal gland . It is also known that ACTH inhibits the uptake of ascorbic acid by isolated rat adrenal glands or isolated rats adrenocortical cells .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have suggested that ascorbic acid in the liver of rats with WIRS is, at least in part, released from the tissue into the bloodstream . It has also been suggested that a single ACTH administration and acute release of ACTH from the pituitary after acute stress might cause an acute release of ascorbic acid from liver tissues into bloodstream in rats . Therefore, it cannot be ruled out that the release of ascorbic acid from the liver tissue of rats with WIRS contributes to the increase in serum ascorbic acid concentration found in the stressed rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations